Risk Factors of Diabetes Mellitus in Urban Communities in Indonesia (IFLS 5) - Armya Zakiah Safitri; Risna Nur Fajariyah; Erni Astutik (Jurnal Berkala Epidemiologi, 2021)
Background: Over the last decades, the number of new diabetic cases and the prevalence of diabetes have tended to increase. The diabetes prevalence rate in Indonesia in 2020 reached 6.20%. Purpose: The aim of this study is to examine the relationship between the variables of age, level of education, smoking status, and Body Mass Index (BMI) and the prevalence of diabetes in the urban areas. Methods: This was a cross-sectional study and used secondary data from the Indonesia Family Life Survey (IFLS 5) in 2015. The data was analyzed using descriptive analysis and simple logistic regression. The dependent variable in this study was Diabetes Mellitus (DM); the independent variables were age, education level, smoking status, and BMI. Results: In terms of the respondents’ characteristics, individuals were mainly over 35 years of age (130 respondents, 83.87%). The highest level of education was attained by 93 respondents (60.00%). There was a correlation between respondents who were over 35 years of age, with p=0.01; prevalence ratio (PR)=5.60; 95%Cl=3.64–8.62) and the level of education (p=0.01; PR=1.69; 95%Cl=1.22–2.34) with the incidence of diabetes in urban areas in Indonesia. There was no correlation between the smoking status (p=0.55; PR=0.67; 95%Cl=0.01–2.73) and the BMI of respondents with the prevalence of diabetes in urban areas in Indonesia. Conclusion: The age and the level of education were linked to the incidence of diabetes in urban areas in Indonesia.